New frontiers in contemporary missiology: Southern African perspectives - D.N. Andrew (Acta Theologica)
The book "New frontiers in contemporary missiology: Southern African perspectives" by Mbaya, H. (Ed.), (UJ Press, 2024), pp. 128, ISBN 978-1-7764896-3-3 is reviewed.